2021
DOI: 10.1123/jab.2020-0365
|View full text |Cite
|
Sign up to set email alerts
|

Biodynamic Responses to Whole-Body Vibration Training: A Systematic Review

Abstract: In recent years, whole-body vibration (WBV) training has received an increasing interest in the sports and medical fields. However, there has been inconsistency among several studies regarding the effect of WBV training on the human body, which is partly due to the lack of the existence of guidelines for using WBV training machines. To understand the effect of WBV training on the human body and build the needed regulations, it is essential first to understand the biodynamic responses to vibration which represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Whole-body shaking(WBV) instruction has gained popularity in the sports and medical fields in recent years (2). Whole-body shaking (WBV) dated identified as effectual possible application method to resistance movement due to its capacity to increase energy, generate cubic mass in voluntary muscle, increase cartilage density, improve cardiovascular function (4).…”
Section: Image Of Whole Body Vibratormentioning
confidence: 99%
See 2 more Smart Citations
“…Whole-body shaking(WBV) instruction has gained popularity in the sports and medical fields in recent years (2). Whole-body shaking (WBV) dated identified as effectual possible application method to resistance movement due to its capacity to increase energy, generate cubic mass in voluntary muscle, increase cartilage density, improve cardiovascular function (4).…”
Section: Image Of Whole Body Vibratormentioning
confidence: 99%
“…The research clearly demonstrated that, despite their long-term consequences, vibration programme workouts are secure, practicable, and well tolerated by patients with various diseases (1). To understand the impact of WBV training on the human body and to develop the necessary rules, it is necessary to first understand biodynamic reactions to vibration, which depict how vibration is conveyed to human body and through the human body (2). The whole body vibration machine works on the principle of vibration and this vibration causes systemic changes/effect in our body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In addition, vibration transferring usually depends on acceleration, transmissibility, interface force, apparent mass during different vibration settings, body posture, age, gender, frequency content, entrance direction, and seat reactions at the vibration entrance place. [5][6][7] Vibrations with a lower than 12 Hz frequency influence the entire body, while vibrations with a frequency higher than 12 Hz mainly have local effects. 7,8 Prolonged exposure to whole-body vibration, has a strong correlation with low back pain.…”
Section: Introductionmentioning
confidence: 99%